Pregnant Women With Low Back Pain Have the Risk of Incontinent Urine in Leuwiliang District, Bogor West Java - Dwi Ratna Sari Handayani; Hafna Rosyita; Dewi Atika Putri; Imam Waluyo; Muhamad Arsyad Subu (Ridwan Institute, 2023)
Objective: This study aims to determine the risk of low back pain complaints on the incidence of urinary incontinence in pregnant women in Leuwiliang District, Bogor. Methods: This study is case contro . with a total sample of 72 pregnant women (case = 36, control = 36) data collection using the Oswestry Disability Index for Low Back pain questionnaire and Questionnare For Female Urinary Incontinence Diagnosis. Results: The results showed that the incidence or complaints of low back pain was 2.08 times more at risk of urinary incontinence, with a p-value = 0.144. 0.144 is not significant (OR = 2.0805% CI = 0.779-5.552 P = 0.144). 0,144 ). Conclusion: This study shows that there is a risk of complaints of Low back Pain on the incidence of Urinary Incontinence which has a risk of 2.08 times but is not significant statically (P=0,144).